Electrochemical Behaviour of the Bactericidal Cefoperazone and its Selective Voltammetric Determination in Pharmaceutical Dosage Forms and Human Serum - Dogan, Burcu; Golcu, Aysegul; Dolaz, Mustafa; Ozkan, Sibel A. (Current Pharmaceutical Analysis, 2009)
Cefoperazone sodium is irreversibly oxidized at the glassy carbon electrode in various buffer systems and at different pH values using cyclic, linear sweep, differential pulse and square wave voltammetric techniques. The oxidation of cefoperazone sodium was irreversible and exhibited diffusion controlled process depending on pH. A detailed oxidation mechanism was proposed and discussed. The dependence of peak current and potentials on pH, concentration, scan rate, nature of the buffer was investigated. According to the linear relationship between the peak current and the concentration, differential pulse (DPV) and square wave (SWV) voltammetric methods for cefoperazone sodium assay in pharmaceutical dosage forms and biological fluids were developed. The determination of cefoperazone sodium was proposed in phosphate buffer at pH 2.00, which allows quantitation over the 4x10-6 - 2x10-5 M and 4x10-6 - 6x10-5 M ranges in supporting electrolyte for DPV and SWV, respectively, and 4x10-6 - 2x10-5 M in spiked serum samples for both techniques. The repeatability, reproducibility, precision and accuracy of the methods in all media were investigated. Precision and accuracy of the developed method were used for the recovery studies. The standard addition method was used for the recovery studies. No electroactive interferences were found in biological fluids from the endogenous substances and additives present in pharmaceutical dosage form.
Keywords: Oxidation